Plane-by-Plane Written, Low-Loss Polymer Optical Fiber Bragg Grating Arrays for Multiparameter Sensing in a Smart Walker - Leal, Arnaldo G.; Frizera, Anselmo; Theodosiou, Antreas; Díaz, Camilo; Jimenez, Mario; Min, Rui; Pontes, Maria José; Kalli, Kyriacos; Marques, Carlos (My University, 2019)
In this paper, we report the development of fiber Bragg gratings (FBGs) arrays in polymer optical fibers (POFs), specifically cyclic transparent optical polymer (CYTOP) fibers, using a femtosecond (fs) laser. The CYTOP is almost transparent to near-ultraviolet and visible light, thus femtosecond lasers appear to be a very promising technology for the development of gratings in such fibers. Bearing this in mind, we have applied the direct write, plane-by-plane inscription method to obtain 'single-peak' FBGs in long arrays. Following this, we examine the performance of a 5-FBG array applied in a smart walker (SW) and characterized for four different functionalities of the proposed healthcare device. The polymer sensors were used to analyze 1) structural health monitoring (SHM) of the SW's mechanical structure; 2) detection of users' movement intention; 3) gait cadence estimation; and 4) detection of floor-induced vibrations for localization and mapping applications. The good results obtained in comparison to commercially available devices show the suitability of the proposed FBG-array on the instrumentation of healthcare devices, where multiple parameters can be measured using the same fiber, which leads to a compact and energy efficient system.
Keywords: Fiber Bragg gratings; Healthcare devices; Polymer optical fibers; Smart walkers